On the peak strength of 7050 aluminum alloy: mechanical and corrosion resistance - Barbara Rivolta; Riccardo Gerosa; Marco Boniardi; Andrea Casaroli (Fracture and Structural Integrity)
This work consists of an experimental study on the ageing response and resulting properties of AA7050 plate material. New heat treatments are investigated for achieving a peak-aged temper, as a T6 temper may be said to be, that achieves yield and tensile strengths superior to those of the documented T7 treatments. For this alloy, the Standard establishes T7X tempers which were developed to obtain a very good compromise between mechanical strength and corrosion resistance. Nevertheless, for all those applications in which the environment is not considered critical for corrosion behaviour, the peak strength condition could be beneficial. In this experimental work, the authors use standard hardness testing to investigate mechanical response as a function of ageing time at several ageing temperatures, all applied immediately after solution. Upon identifying specific times and temperatures of interest, specimens aged under the selected treatments were subjected to tensile testing and intergranular corrosion testing. The results show that a single-step ageing heat treatment is able to produce a significantly high both yield and ultimate tensile strength. Moreover, the corrosion test data indicates that this new heat treatment produces corrosion resistance similar to that of the T76 heat treatment.